A review on the plant resources of important medicinal licorice. (30th January 2023) - Yan, Binbin; Hou, Junling; Li, Wenbin; Luo, Lin; Ye, Min; Zhao, Zhongzhen; Wang, Wenquan
Abstract: Ethnopharmacological relevance: Glycyrrizae Radix et Rhizoma has various effects, including tonifying the spleen and qi, clearing heat and toxic substances, eliminating phlegm, relieving cough and pain, and harmonizing the effects of other medicines. It is widely used in the pharmaceutical and food industries. Aims of the study: This review systematically collates the identification of Glycyrrhiza Linn. species with medicinal value and their distributions. The morphological and genetic characteristics, distribution, quantity of reserves in China, suitable environment, and area of suitable habitat of important medicinal species were reviewed. The effects of the natural environment and cultivation management (water and nutrients) on the growth and quality of licorice were reviewed. The aim is to make people have a systematic understanding of the status of medicinal plant resources of the G. Linn., and understand the natural and human factors that affect its quality, so as to provide help for the collection of resources of the important medicinal licorice and the human control of its quality in the future. Materials and methods: We conducted extensive searches of the primary literature, master's and doctoral theses, and pharmacopeias of many countries using PubMed, Geenmedical, CNKI, Web of Science, SCI-hub and other databases. The keywords used in searches included "classification of Glycyrrhiza, " "medicinal Glycyrrhiza, " "distribution of Glycyrrhiza, " and "suitable environment for Glycyrrhiza " The results of research conducted by our research group on the morphological and genetic characteristics, natural distribution, and effects of artificial regulation on the growth and quality of licorice were summarized. Results: There are approximately 29 species of G. Linn. worldwide, including 15 species with medicinal value. These species occur on all continents except Antarctica across 41 countries. Only one licorice is recorded in Indian pharmacopoia, two species are recorded in US and Japanese pharmacopoeias, and three species are recorded in most national pharmacopoeias: G. glabra Linn., G. uralensis Fisch. and G. inflata Batalin. These three medicinal licorice species are mainly distributed in Eurasia, especially Central Asia. The main morphological differences between these three medicinal licorice species are in the leaves, inflorescences, pods, and seeds, and they can be distinguished by ITS and psbA-trnH sequences. The reserves of wild licorice in China have decreased annually to 1.04 million(t) in 2010. The cultivation area of G. uralensis Fisch in China is currently approximately 26, 900 hm 2 . Soil conditions have a substantial effect on the yield and quality of G. uralensis Fisch, especially water and nutrients. Appropriate irrigation and fertilization measures can enhance the quality of G. uralensis Fisch. Conclusions: G. Linn. species and their natural distributions were summarized. The morphology, genetic characteristics, suitable environment, and area of suitable habitat of three medicinal licorice species collected in major countries were described. The main environmental conditions and cultivation measures affecting their growth and medicinal quality were determined. This article provides a comprehensive review on G. Linn. medicinal plant resources to enhance the future use of these resources.